Potassium silicate-based fireproof glass and method for manufacturing the same
Patent Information
- Application Number
- CN202611165687.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0008]针对现有技术存在的不足,本发明提供了一种硅酸钾基防火玻璃及其制备方法,本发明通过在液相环境中将含锡前驱体、含锑前驱体与螯合抑制剂进行配位反应,形成表面包覆有机基团的金属络合物,再经水解-缩聚反应原位生成表面含有金属-羟基掺锑二氧化锡纳米颗粒,并同步利用其表面金属-羟基与硅酸钾三维网络中Si-OH的脱水缩合反应,形成Si-O-Sn键和Si-O-Sb键的共价氧桥键,将ATO纳米颗粒化学键合锁定于硅酸钾凝胶网络中,得到优异的隔热性能、防火性能及长期服役稳定性硅酸钾基防火玻璃,克服了功能填料分散性不足产品存在的对环境热辐射的调控能力缺失以及长期服役稳定性不足的问题
1、本发明提供了一种硅酸钾基防火玻璃的制备方法,在液相环境中,将含锡前驱体、含锑前驱体与螯合抑制剂混合,并进行配位反应,形成表面包覆有机基团的金属络合物,得到前驱体混合液;含锡前驱体与含锑前驱体的摩尔比为8~12:1,螯合抑制剂与含锡前驱体的摩尔比为0.5~2:1;其中,这些基团赋予ATO纳米颗粒与硅酸钾前驱体溶液的优异相容性,使其能够在硅酸钾前驱体溶液中均匀铺展,实现了功能填料ATO纳米颗粒的均匀分散。
Smart Images

Figure CN122976128A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fire-resistant glass technology, specifically to a potassium silicate-based fire-resistant glass and its preparation method. Background Technology
[0002] Fire-resistant glass is a key material for building fire safety, widely used in high-rise building curtain walls, fire-resistant partitions, and fire-resistant doors and windows. Traditional grout-filled fire-resistant glass relies on alkaline silicate adhesive to foam and ceramicize during a fire to achieve fire resistance. However, its function is limited, lacking solar heat radiation blocking capabilities in everyday use, requiring additional shading facilities, resulting in system redundancy and increased costs. Integrating thermal insulation and fire resistance into a single glass component, achieving integrated "thermal insulation-fire resistance," is a crucial technological path for driving the evolution of traditional fire-resistant glass into high-performance building functional materials.
[0003] In the prior art, an anti-reflective heat-insulating fireproof glass and its preparation method (CN202511098529.6) prepares an anti-reflective film layer on both sides of the heat-insulating fireproof glass, which improves the light transmission performance of the fireproof glass. However, the pure physical film layer can only passively reduce reflection and lacks the ability to actively absorb and regulate solar heat radiation. Moreover, the exposed surface coating is easily corroded and peeled off by the natural environment, resulting in insufficient stability during long-term service.
[0004] A heat-insulating fireproof glass and its manufacturing method (CN202411652910.8) adopts a structure in which a polyacrylamide gel layer is filled between a fire-facing glass layer and an unfacing glass layer. By introducing octaaminoPOSS and polydopamine-modified tetraneedle zinc oxide whiskers as functional fillers, a hybrid heat-insulating layer is constructed. However, this technology introduces powder by direct blending, and solid particles are prone to agglomeration and sedimentation in the gel system, resulting in poor dispersibility of functional fillers. In addition, organic polymer gels such as polyacrylamide are prone to degradation and aging during thermal cycling.
[0005] An energy-saving nano fireproof and heat-insulating glass (CN202221566772.8) has an infrared blocking layer and an ultraviolet blocking layer, a nano film and a high-temperature polyester film attached to the outside, and a heat insulation groove is opened on the borosilicate glass substrate to form a heat insulation cavity to block heat conduction; however, this technology relies on a static physical hollow structure and film layer superposition, and cannot dynamically respond to and effectively control heat radiation according to changes in ambient temperature.
[0006] A thermochromic fireproof canopy glass (CN202323199346.2) has a multi-layered composite structure stacked from the outside to the inside. It utilizes a heat-insulating PVB layer to absorb infrared light, and a thermochromic film layer that changes color when heated to selectively transmit light and reduce solar heat radiation. However, due to its single response point, it is difficult to accurately control the ambient heat radiation. Furthermore, the core organic PVB layer and thermochromic film are prone to thermal aging and fatigue failure under long-term alternation of hot and cold and light cycles, resulting in insufficient long-term service stability.
[0007] In summary, the existing technology for producing heat-insulating and fire-resistant glass has the following technical defects: insufficient dispersion of functional fillers, lack of ability to regulate environmental heat radiation, and insufficient long-term service stability. Summary of the Invention
[0008] To address the shortcomings of existing technologies, this invention provides a potassium silicate-based fireproof glass and its preparation method. This invention involves a coordination reaction between a tin-containing precursor, an antimony-containing precursor, and a chelation inhibitor in a liquid environment to form a metal complex coated with organic groups. This complex is then subjected to a hydrolysis-condensation reaction to generate antimony-doped tin dioxide nanoparticles with metal-hydroxyl groups on their surface in situ. Simultaneously, the surface metal-hydroxyl groups undergo a dehydration condensation reaction with Si-OH groups in the three-dimensional network of potassium silicate, forming covalent oxygen bridges of Si-O-Sn and Si-O-Sb bonds. This chemically bonds and locks the ATO nanoparticles within the potassium silicate gel network, resulting in a potassium silicate-based fireproof glass with excellent thermal insulation, fire resistance, and long-term service stability. This overcomes the problems of insufficient functional filler dispersion, such as lack of control over environmental thermal radiation and insufficient long-term service stability. Furthermore, the preparation method of this invention overcomes the problem of uneven dispersion of functional fillers.
[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first objective of this invention is to provide a method for preparing potassium silicate-based fire-resistant glass, comprising the following steps: S1. In a liquid phase environment, a tin-containing precursor, an antimony-containing precursor, and a chelation inhibitor are mixed. The Sn in the tin-containing precursor... 4+ Sn 2+ and Sb in antimony-containing precursors 3+ A coordination reaction occurs with the chelation inhibitor, where the organic ligands of the chelation inhibitor partially replace the anionic ligands in the tin-containing and antimony-containing precursors, forming a metal complex with surface-coated organic groups, yielding a precursor mixture. Tin and antimony are fundamental elements in the synthesis of ATO nanomaterials, and the organic solvent provides a homogeneous liquid-phase reaction environment. The anionic ligands in the tin-containing and antimony-containing precursors: If the precursors are chlorides (SnCl4, SbCl3), then the original anionic ligands refer to chloride ions (Cl...). -If the precursor is acetate or nitrate, it refers to the acetate ion (CH3COO). - ) or nitrate ions (NO3) - ).
[0010] S2. A hydrolysate composed of water and an organic solvent is added dropwise to a precursor mixture, and a hydrolysis-condensation reaction is carried out. During the reaction, water molecules nucleophilically replace the metal complexes coated with organic groups on the surface, gradually replacing some of the chelation inhibitor ligands and residual anionic ligands (anionic ligands in tin-containing and antimony-containing precursors), exposing the metal center and generating intermediates containing active metal-hydroxyl groups. Dehydration condensation or deacidification condensation occurs between the intermediates, forming an inorganic oxide network containing Sn-O-Sn, Sn-O-Sb, or Sb-O-Sb bond structures. As the condensation reaction continues, antimony-doped tin dioxide (ATO) homogeneously nucleates and grows from the supersaturated sol. The chelation inhibitor ligands that are not completely replaced accumulate on the surface of the crystal nuclei, and the resulting steric hindrance effect counteracts the thermodynamic driving force of grain growth, causing the crystal nuclei to be kinetically locked and terminated at the nanoscale, forming antimony-doped tin dioxide nanoparticles (ATO nanoparticles), and obtaining an ATO precursor solution.
[0011] S3. Mix potassium silicate precursor solution, ATO precursor solution, crosslinking agent, and water to obtain a composite fire retardant liquid; fill the cavity formed by bonding two layers of glass sheets with the composite fire retardant liquid, seal it, and allow it to cure statically to obtain potassium silicate-based fire retardant glass. The static curing of the composite fire retardant liquid is essentially a heat-driven three-dimensional crosslinking and sol-gel phase transition process. Driven by activation energy provided at 40℃~60℃, the active silanol groups in the potassium silicate precursor solution undergo deep dehydration condensation reaction, generating high-bond-energy covalent oxygen bridges. This promotes the interweaving of oligomeric silicate chains, constructing a three-dimensional inorganic covalent network of silicates. As the cross-linking density of the three-dimensional inorganic covalent network of silicates continuously increases, the viscosity of the system tends to infinity and completely loses its macroscopic fluidity, ultimately transforming the composite fire retardant liquid from a liquid sol into a solid gel. During the transformation, the strongly alkaline environment gradually removes the surface-coated organic groups. The exposed metal-hydroxyl groups on the surface of the ATO nanoparticles undergo dehydration condensation with the Si-OH groups on the potassium silicate three-dimensional network under strongly alkaline conditions, forming interfacial connections containing Si-O-Sn, Si-O-Sb, or Sb-O-Sb structures. This fixes the ATO nanoparticles within the silicate three-dimensional network, reducing their migration, aggregation, and sedimentation tendencies. Sealing is to prevent moisture evaporation during the curing process.
[0012] The addition of crosslinking agent promotes the condensation and crosslinking between potassium silicate molecules, and at the same time induces the Si-OH on the potassium silicate network to undergo dehydration condensation with the metal-hydroxyl groups on the surface of ATO nanoparticles, forming a potassium silicate gel system with mechanical strength and a three-dimensional network structure containing Si-O-Sn bonds and Si-O-Sb bonds.
[0013] Preferably, the molar ratio of tin-containing precursor to antimony-containing precursor is 8-12:1, and the molar ratio of chelation inhibitor to tin-containing precursor is 0.5-2:1. The molar ratio of tin-containing precursor to antimony-containing precursor directly determines the concentration of antimony substitutional doping for tin in the in-situ generated ATO nanolattice, thereby regulating the carrier concentration and plasma resonance frequency, ultimately affecting near-infrared absorption performance. When the molar ratio is below 8:1 (i.e., antimony doping is relatively excessive), the excess Sb... 3+ Unsubstituted antimony cannot completely substitute into the SnO2 lattice, and some antimony exists as interstitial atoms or independent oxide phases, leading to increased lattice distortion. On the one hand, non-substituted antimony cannot contribute free electrons, resulting in saturation or even a decrease in carrier concentration, and weakening of the plasma resonance effect. On the other hand, Sb... 3+ The introduction of dd-electron transitions and defect energy levels causes the intrinsic absorption edge of the material to redshift into the visible light region, resulting in the color of ATO powder deepening from light blue-gray to grayish-black, ultimately reducing the visible light transmittance of fireproof glass. When the molar ratio is higher than 12:1 (i.e., insufficient antimony doping), Sb in the lattice... 5+ Effective substitution Sn 4+ With too few sites, the carrier concentration is below the threshold required to establish strong plasma resonance, and the dielectric loss and light absorption efficiency in the infrared band are significantly insufficient, making it impossible to form an effective infrared radiation shielding barrier, which leads to the deterioration of the solar infrared heat blocking performance of fireproof glass.
[0014] Chelation inhibitors, through coordination with tin and antimony metal ions, moderately and precisely encapsulate and regulate the reactive sites of the metal centers. On the one hand, the steric hindrance effect of the chelating ligands can shield some coordinated water molecules, inhibit the hydroxylation rate, and prevent explosive hydrolysis of the precursor mixture when the hydrolysate is added. On the other hand, the retained active sites ensure that the hydrolysis-condensation reaction can continue under mild conditions of 30℃~60℃, thereby controlling the matching of the nucleus generation rate and the crystal growth rate, and realizing the uniform nucleation and controllable growth of ATO nanoparticles. When the proportion of chelating inhibitor is too low (i.e., molar ratio below 0.5:1), the chelation protection of the metal center is insufficient, and a large number of exposed active coordination sites exist in the system. During the addition of the hydrolysate, the rate of coordination substitution between water molecules and metal ions far exceeds the controllable range, triggering a violent and explosive hydrolysis reaction. This leads to the instantaneous generation of a large number of crystal nuclei and an uncontrolled growth rate, ultimately forming micron- or submicron-sized aggregates with wide particle size distributions and easy agglomeration, severely degrading the dispersion uniformity of ATO nanoparticles in the potassium silicate matrix. When the proportion of chelating inhibitor is too high (i.e., molar ratio above 2:1), the chelating ligands become over-coordinated and saturated with the metal center, significantly increasing the activation energy barrier of the hydrolysis and condensation reactions. Within the process temperature window of 30℃ to 60℃, the reaction kinetic rate drops sharply, crystal nuclei are difficult to form, and crystal growth stagnates, making it impossible to obtain ATO nanoparticles with a definite crystal phase structure. Meanwhile, excessive organic chelating molecules remain largely in the inorganic framework after the potassium silicate gel solidifies, forming an organic-inorganic hybrid phase. This organic phase undergoes thermal decomposition and combustion under high-temperature fire conditions, generating smoke and destroying the dense ceramic structure of the potassium silicate gel network, resulting in a significant decrease in the fire resistance integrity of the heat insulation and fireproof layer.
[0015] Preferably, the volume ratio of water to organic solvent is 1:3 to 8, and the molar ratio of water to tin-containing precursor is 2 to 4:1. This ratio synergistically regulates the local spatial concentration of water molecules and the stoichiometry of reactants in the hydrolysis system. Diluting water with a large amount of organic solvent can act as a "physical buffer" during the dripping process: in conjunction with the chelation inhibitor added in the early stage, it ensures that water molecules can only slowly and uniformly attack the metal precursor, achieving in-situ uniform nucleation; below this range (i.e., too little solvent and too high water concentration), the local concentration of water molecules is too high, which will break through the steric hindrance protection of the chelating agent, causing uncontrolled hydrolysis of the metal precursor, which will trigger the rapid growth of nanoparticles and produce macroscopic irreversible aggregation; above this range (i.e., too much solvent and too dilute system), the concentration of reactants in the system is excessively diluted, which leads to a decrease in the rate of sol-gel condensation reaction, prolongs the reaction cycle, and may even lead to insufficient development of the potassium silicate three-dimensional cross-linked network, insufficient cross-linking density and mechanical strength of the gel skeleton, and a decrease in effective solid content, ultimately affecting the stability of the composite fireproof liquid injection process and the structural density of the fireproof layer after curing.
[0016] The molar ratio of water to tin-containing precursor determines the theoretical degree of hydrolysis (thermodynamic degree) of the system. From a stoichiometric perspective, 2 mol of water is theoretically required to generate tin oxide. Setting this range ensures sufficient hydrolysis to convert into metallic hydroxyl groups while avoiding particle agglomeration caused by excessive free water. Below this range (i.e., insufficient water), the hydrolysis reaction is incomplete, resulting in a large number of unreacted halogen groups or organic groups remaining on the metal atoms, blocking the continuous condensation of Sn-O-Sn and Sn-O-Sb bonds, leading to a significant decrease in the infrared heat insulation performance of the final glass. Above this range (i.e., severely excessive water), there is a large amount of free water in the system. Excessive water will cause over-hydrolysis, causing the crystal nuclei to lose their steric protection and undergo secondary agglomeration and continuous growth, breaking the nanoscale size limit, and ultimately leading to filler sedimentation failure.
[0017] Preferably, when preparing the precursor mixture, the liquid phase environment is provided by an organic solvent, which is selected from at least one of anhydrous ethanol, isopropanol, and ethylene glycol methyl ether, all of which are of analytical grade.
[0018] Preferably, when preparing the ATO precursor solution, the organic solvent is selected from at least one of anhydrous ethanol, isopropanol, and ethylene glycol methyl ether, all of which are of analytical grade.
[0019] Preferably, the mass ratio of potassium silicate precursor solution, ATO precursor solution, crosslinking agent and water is 1:0.02~0.25:0.005~0.04:0.08~0.35. The mass ratio of the ATO precursor solution determines the loading concentration of the thermal insulation filler (ATO) in the potassium silicate-based fireproof glass. This ensures the formation of a sufficiently dense near-infrared absorption network within the system, while preventing the continuity of the silicate matrix from being disrupted by excessive filler. If the concentration is below this range (i.e., too little ATO), the total number of charge carriers capable of plasma resonance in the system is insufficient, failing to form an effective thermal radiation blocking barrier, leading to a sharp increase in the total solar infrared thermal transmittance of the glass. If the concentration is above this range (i.e., too much ATO), two fatal consequences will occur: first, high concentrations of nanoparticles will drastically shorten the free path between particles, significantly increasing the probability of collision and aggregation, resulting in severe Rayleigh scattering on a macroscopic scale; second, excessive external filler will disrupt the three-dimensional network of the potassium silicate matrix, causing a decrease in the strength of the cured gel layer, making it prone to collapse under high fire temperatures and losing its fireproof integrity.
[0020] The mass ratio of the crosslinking agent determines the crosslinking density of the inorganic gel network and the kinetic rate of the curing reaction. Adding a small amount can increase the crosslinking density of the cured fireproof gel. If it is below this range (i.e., the degree of crosslinking is insufficient), the crosslinking density of the potassium silicate solution is too low, the gel network is too loose and the strength is poor, and it is easy to cause the sedimentation of ATO nanoparticles during long-term service. If it is above this range (i.e., the crosslinking is too high), the solution will rapidly crosslink and gel during the mixing stage, and the viscosity will increase rapidly. Not only will the internal air bubbles be unable to be removed by vacuum, but the fluidity will be completely lost, making it impossible to complete the 5mm pouring process.
[0021] The ideal water mass ratio dilutes the solution viscosity to a fluid state suitable for degassing and injection, while also ensuring that, in the event of a fire, the vaporization of this water promotes the expansion and foaming of the silicate matrix, forming a porous insulating ceramic layer. Below this range: the viscosity of the composite fire retardant is too high, resulting in extremely high resistance to ultrasonic and vacuum degassing, leaving a large number of microbubbles in the solution. This leads to dense light spots and reduced light transmittance in the cured glass. Excessive viscosity also causes injection difficulties and uneven cavity filling. Above this range: excessive water is introduced, reducing the solid content of the gel. This can cause volume shrinkage during curing, generating internal stress that leads to glass delamination. Furthermore, excessively low solid content results in an overall decrease in fire resistance.
[0022] Preferably, silica sol is mixed with potassium hydroxide solution to obtain potassium silicate precursor solution; in potassium silicate precursor solution, the mass fraction of silica sol is 68wt%~73wt% and the mass fraction of potassium hydroxide solution is 27wt%~32wt%.
[0023] Preferably, the conditions for the coordination reaction are: stirring at room temperature for 3 to 5 hours.
[0024] Preferably, the hydrolysis-condensation reaction conditions are: stirring at 30℃~60℃ for 2h~6h.
[0025] Preferably, the tin-containing precursor is selected from tin tetrachloride or stannous chloride, both of which are of analytical grade.
[0026] Preferably, the antimony-containing precursor is selected from antimony trichloride or antimony acetate, both of which are of analytical grade.
[0027] Preferably, the silica sol is an alkaline silica sol with a solid content of 50 wt%, a Na2O content of less than 0.3 wt%, a pH of 9.0~10.0, and an average particle size of 90 nm~110 nm.
[0028] Preferably, the chelation inhibitor is selected from acetylacetone, diethanolamine, or triethanolamine.
[0029] Preferably, the potassium hydroxide solution is an aqueous solution prepared from analytical grade potassium hydroxide solid and deionized water, with a potassium hydroxide concentration of 50%. The system of this invention prepares potassium silicate-based fire-resistant glass, therefore a potassium hydroxide solution must be used; for other types of fire-resistant glass, other alkali metal hydroxide solutions can be used instead.
[0030] Preferably, the crosslinking agent is at least one of borax and boric acid, both of which are of analytical grade and have an average particle size of 20 μm to 75 μm.
[0031] Preferably, the curing conditions are: static curing at 40℃~60℃ for 12h~24h.
[0032] Preferably, the glass substrate comprises: SiO2 70wt%~75wt%, Na2O 12wt%~15wt%, CaO 7wt%~10wt%, MgO 2wt%~5wt%, and Al2O3 0.5wt%~2.5wt%. This glass substrate is architectural float glass, and the listed components are the main components. Trace impurities are unavoidable during the glass melting process, and these impurities mainly consist of ferric oxide and potassium oxide.
[0033] Preferably, the thickness of the glass sheet is 1mm to 5mm, and the visible light transmittance is greater than 90%.
[0034] Preferably, after mixing the potassium silicate precursor solution, ATO precursor solution, crosslinking agent, and water, ultrasonic dispersion and vacuum degassing are performed. The vacuum degassing conditions are: vacuum degassing for 20 to 40 minutes at a vacuum degree of -0.09 MPa to -0.1 MPa. The principle of ultrasonic dispersion is used to break up the agglomeration of ATO nanoparticles, achieving uniform nanoscale dispersion within the potassium silicate matrix; vacuum degassing is used to eliminate microbubbles introduced during the mixing and ultrasonic treatment processes.
[0035] Preferably, two layers of glass sheets are spliced and bonded together using a sealant to form a cavity with a sealant injection port; wherein the sealant is selected from butyl rubber sealant or silicone sealant.
[0036] A second objective of this invention is to provide a potassium silicate-based fireproof glass prepared by the above-described method.
[0037] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a method for preparing potassium silicate-based fireproof glass. In a liquid environment, a tin-containing precursor, an antimony-containing precursor, and a chelation inhibitor are mixed and subjected to a coordination reaction to form a metal complex with organic groups coated on its surface, resulting in a precursor mixture. The molar ratio of the tin-containing precursor to the antimony-containing precursor is 8-12:1, and the molar ratio of the chelation inhibitor to the tin-containing precursor is 0.5-2:1. These groups impart excellent compatibility between ATO nanoparticles and the potassium silicate precursor solution, enabling them to spread uniformly in the potassium silicate precursor solution, thus achieving uniform dispersion of the functional filler ATO nanoparticles.
[0038] A hydrolysate, consisting of a mixture of water and an organic solvent, is dropwise added to a precursor mixture to induce a hydrolysis-condensation reaction, generating an intermediate containing metal-hydroxyl groups. This intermediate then undergoes intermolecular dehydration or deacidification condensation reactions to produce antimony-doped tin dioxide nanoparticles containing metal-hydroxyl groups, yielding an ATO precursor solution. In the hydrolysate, the volume ratio of water to organic solvent is 1:3–8, and the molar ratio of water to the tin-containing precursor is 2–4:1. A potassium silicate precursor solution, an ATO precursor solution, a crosslinking agent, and water are mixed to obtain a composite fire retardant liquid. This composite fire retardant liquid is then filled into two layers of glass. Within the cavity formed by bonding the glass sheets, the mixture is sealed and allowed to solidify. During this process, the composite fireproof liquid transforms from a liquid sol into a solid gel. Potassium silicate undergoes condensation to form a three-dimensional potassium silicate network. Simultaneously, the metal-hydroxyl groups on the surface of the antimony-doped tin dioxide nanoparticles undergo dehydration condensation with the Si-OH groups on the potassium silicate three-dimensional network, forming a gel containing Si-O-Sn, Si-O-Sb, and Sb-O-Sb bonds. This chemically bonds and locks the ATO nanoparticles within the potassium silicate three-dimensional network, thereby inhibiting the aggregation and sedimentation of the ATO nanoparticles and yielding potassium silicate-based fireproof glass.
[0039] Furthermore, the potassium silicate-based fireproof glass provided by this invention possesses excellent heat insulation, fire resistance, and long-term service stability, overcoming the problems existing in the prior art. Specifically, in terms of optical and heat insulation performance, it exhibits a visible light transmittance of 80%~88%, haze below 5%, and a total solar infrared thermal energy transmittance of 15%~35%, maintaining high visible light transmittance and low haze while possessing excellent solar heat radiation blocking capability. Regarding fire resistance, it achieves a fire resistance integrity ≥90 min, an average temperature rise of ≤140℃ on the unexposed surface for ≥60 min, and no smoke release or dripping at high temperatures. In terms of weather resistance, after 1000 hours of UV aging, the transmittance decreases by ≤3%, and after 500 hours of damp heat aging, there is no delamination, blistering, or ATO nanoparticle precipitation. After 1000 cycles of heating and cooling from -20℃ to 60℃, the near-infrared blocking rate decreases by ≤2%.
[0040] 2. In the preparation method provided by this invention, tin-containing precursors and antimony-containing precursors (metal alkoxides or inorganic salts) are prone to violent and uncontrollable hydrolysis when exposed to water, resulting in the formation of large-particle precipitates instead of a transparent sol. The chelation inhibitor reduces the reactivity of metal ions by coordinating with them, thereby effectively slowing down and controlling the subsequent hydrolysis rate and ensuring the uniformity and high transmittance of the final sol.
[0041] 3. The preparation method of the present invention is simple, mild, easy to scale up industrially, and does not require major modifications to existing fireproof glass production lines. Attached Figure Description
[0042] Figure 1 The image shows a SEM-EDS surface scan of the composite fire retardant liquid cured in the potassium silicate-based fire retardant glass of Example 1, where a is the SEM image, b is the element O, c is the element Si, d is the element K, e is the element Sb, and f is the element Sn.
[0043] Figure 2 The image shows a TEM image of the composite fire retardant liquid cured in the potassium silicate-based fire retardant glass of Example 1, where a is a TEM image, b is Sn element, c is O element, and d is Sb element.
[0044] Figure 3 Infrared analysis images of the composite fire retardant liquid cured in the potassium silicate-based fire retardant glass of Example 1 and Comparative Example 1. Detailed Implementation
[0045] The technical solution of the present invention will be clearly and completely described below with reference to the data in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0046] It should be noted that the technical terms used in this invention are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in the following embodiments of this invention can be purchased commercially or prepared by existing methods. The glass substrate mainly comprises 72.3% SiO2, 13.5% Na2O, 8.8% CaO, 3.6% MgO, and 1.2% Al2O3, with a thickness of 5 mm and a visible light transmittance greater than 90%. In the embodiments of this invention, both the fire-facing glass layer and the back-facing glass layer are glass substrates.
[0047] This invention achieves uniform dispersion of functional fillers through in-situ hydrolysis of tin-containing and antimony-containing precursors. After coordination reactions with chelating inhibitors, the tin-containing and antimony-containing precursors undergo hydrolysis-condensation reactions. Incompletely replaced chelating inhibitor ligands (such as hydroxyl, methyl, and alkyl carbon chains) coat the surface of ATO nanoparticles, imparting excellent compatibility between the ATO nanoparticles and the potassium silicate precursor solution, enabling them to spread uniformly in the potassium silicate precursor solution. Furthermore, during the curing process of the composite fire retardant liquid, the potassium silicate undergoes condensation to form a three-dimensional potassium silicate network, further inhibiting the growth and aggregation of ATO nanoparticles. The strongly alkaline environment gradually removes the organic coating layer, exposing the metal hydroxyl groups on the surface of the ATO nanoparticles. These hydroxyl groups then undergo dehydration condensation with the Si-OH groups on the potassium silicate three-dimensional network, forming Si-O-Sn, Si-O-Sb, and Sb-O-Sb bonds. This chemically bonds the ATO nanoparticles within the potassium silicate three-dimensional network, thereby inhibiting their aggregation and sedimentation. Therefore, the prepared potassium silicate-based fire-retardant glass functional filler exhibits good dispersibility. According to the sol-gel theory, highly active silanol groups and metal-hydroxyl groups on the surface of ATO nanoparticles undergo dehydration condensation under strongly alkaline conditions and a curing temperature of 40℃~60℃ to form covalent oxygen bridges. This chemical bonding mechanism is fundamentally different from physical coating or simple blending and is the core structural basis for achieving long-term stable dispersion of ATO nanoparticles in this invention.
[0048] This invention selects potassium silicate gel as the matrix. As the potassium silicate matrix cross-links and solidifies, ATO nanoparticles are in-situ fixed within the three-dimensional gel network, thereby preventing the aggregation of ATO nanoparticles during long-term service. Simultaneously, the inorganic chemical framework eliminates degradation pathways such as photodegradation chain scission, amide hydrolysis, or thermo-oxidative aging. This allows the potassium silicate-based fireproof glass to not only block filler migration, aggregation, and precipitation caused by thermal expansion and contraction during long-term service, but also withstand long-term ultraviolet radiation and be protected from damage under humid and hot conditions. This synergistic mechanism of in-situ fixed ATO nanoparticles and the intrinsic stability of the inorganic network overcomes the limitations of traditional heat-insulating fireproof glass, which relies on easily degradable and aged organic phases and the tendency of blended powders to aggregate, resulting in short weather resistance. Therefore, the potassium silicate-based fireproof glass of this invention exhibits excellent long-term service stability.
[0049] This invention effectively regulates the near-infrared absorption characteristics by controlling the molar ratio of tin-containing and antimony-containing precursors to modulate the lattice doping structure of in-situ generated ATO nanoparticles. Simultaneously, the in-situ hydrolysis process confines the particle size to the nanoscale, significantly reducing Rayleigh scattering in the visible light band of the fireproof glass. This allows the potassium silicate-based fireproof glass to maintain high visible light transmittance and low haze while exhibiting good solar infrared heat blocking performance. This mechanism, which alters infrared absorption characteristics by adjusting the molar ratio in the early stages of synthesis, overcomes the limitation of traditional blending methods, which rely on fixed-doped ATO powder, resulting in untunable spectral characteristics. Therefore, the prepared potassium silicate-based fireproof glass exhibits strong control over environmental thermal radiation.
[0050] The potassium silicate matrix of this invention is a hydrogel system. Conventional SEM characterization requires drastic vacuum dehydration and drying, which causes capillary contraction and damages the original three-dimensional gel network. This inevitably forces particles to passively approach each other, resulting in "pseudo-agglomeration." Consequently, the SEM images after in vitro drying cannot accurately reflect the in-situ dispersion state of the system within the closed cavity. Furthermore, the fire-resistant glass measured in the specification has a visible light transmittance of 80%–88% and a haze of less than 5%. According to the laws of light scattering physics, this excellent optical performance directly proves that the internal ATO nanoparticles have not agglomerated.
[0051] The test standards for the performance indicators involved in the embodiments of this invention are as follows: visible light transmittance and total solar infrared thermal energy transmittance are tested according to GB / T2680-2021 standard; fire resistance, ultraviolet aging performance and damp heat aging performance are tested according to GB / T15763.1-2025 standard.
[0052] To enable those skilled in the art to more clearly understand the technical solution of the present invention, the following will provide a detailed description in conjunction with specific embodiments: Example 1 A method for preparing potassium silicate-based fire-resistant glass includes the following steps: S1. Add tin tetrachloride and antimony trichloride to anhydrous ethanol, then add acetylacetone and stir until completely dissolved to form a precursor mixture; wherein, the molar ratio of tin tetrachloride to antimony trichloride is 11:1, the amount of tin tetrachloride added is 10% of the mass of anhydrous ethanol, and the molar ratio of acetylacetone to tin tetrachloride is 1.1:1; add the hydrolysate prepared by deionized water and anhydrous ethanol at a volume ratio of 1:5 dropwise to the precursor mixture at 50°C, and continue stirring for 4 hours after the addition is complete to obtain the ATO precursor solution; wherein, the molar ratio of deionized water to tin tetrachloride in the hydrolysate is 3:1.
[0053] S2. Mix 70 wt% silica sol with 30 wt% potassium hydroxide solution and stir at 45°C for 35 min to obtain potassium silicate precursor solution.
[0054] S3. After mixing potassium silicate precursor solution, ATO precursor solution, borax and deionized water evenly according to the mass ratio of 1:0.02:0.005:0.15, the mixture is ultrasonically dispersed for 60 min under ultrasonic power of 400W and frequency of 40kHz. After ultrasonication, the mixture is vacuum degassed for 30 min under vacuum of -0.095MPa to obtain composite fire retardant liquid.
[0055] S4. After removing oil and impurities from the edges of the fire-facing glass layer and the unfacing glass layer, butyl rubber sealing strips are used to splice and bond the fire-facing glass layer and the unfacing glass layer to obtain a cavity with an injection port. Then, composite fireproof liquid is injected into the 5mm cavity between the two glass sheets at normal pressure. Then, silicone sealant is evenly injected into the grooves formed around the fire-facing glass layer and the unfacing glass layer to seal the injection port and the grooves. After that, it is left to cure at 50℃ for 18 hours to obtain potassium silicate-based fireproof glass.
[0056] The potassium silicate-based fireproof glass prepared in this embodiment has the following main performance characteristics as tested: visible light transmittance is 88%, haze is 1.5%, total solar infrared thermal transmittance is 35%; fire resistance integrity is 90 min, the duration of average temperature rise on the unexposed surface ≤140℃ is 60 min, no smoke release or dripping is generated at high temperature; after 1000 h of UV aging, the light transmittance decreases by 2.5%; after 500 h of damp heat aging, there is no delamination, no bubbling, and no ATO nanoparticle precipitation; after 1000 cycles of -20℃ to 60℃, the near-infrared blocking rate decreases by 1.8%.
[0057] Example 2 A method for preparing potassium silicate-based fire-resistant glass includes the following steps: S1. Stannous chloride and antimony trichloride are added to isopropanol, and then diethanolamine is added and stirred until completely dissolved to form a precursor mixture. The molar ratio of stannous chloride to antimony trichloride is 8:1, the amount of stannous chloride added is 25% of the mass of isopropanol, and the molar ratio of diethanolamine to stannous chloride is 1.2:1. A hydrolysate prepared by mixing deionized water and isopropanol at a volume ratio of 1:4 is added dropwise to the precursor mixture at 30°C. After the addition is complete, the mixture is stirred for 5 hours to obtain an ATO precursor solution. The molar ratio of deionized water to stannous chloride in the hydrolysate is 2:1.
[0058] S2. Mix 68wt% silica sol with 32wt% potassium hydroxide solution and stir at 50℃ for 30 min to obtain potassium silicate precursor solution.
[0059] S3. After mixing potassium silicate precursor solution, ATO precursor solution, boric acid and deionized water evenly according to the mass ratio of 1:0.25:0.02:0.25, the mixture is ultrasonically dispersed for 45 min under ultrasonic power of 300W and frequency of 28kHz. After ultrasonication, the mixture is vacuum degassed for 20 min under vacuum of -0.1MPa to obtain composite fire retardant liquid.
[0060] S4. After removing oil and impurities from the periphery of the fire-facing glass layer and the unfacing glass layer, the fire-facing glass layer and the unfacing glass layer are spliced and bonded together using butyl rubber sealing strips to obtain a cavity containing the injection port. Subsequently, composite fireproof liquid is injected into the 5mm cavity between the two glass sheets at normal pressure. Then, silicone sealant is evenly injected into the grooves formed around the periphery of the fire-facing glass layer and the unfacing glass layer to seal the injection port and the grooves. After that, it is left to stand and cure at 60℃ for 12 hours to obtain potassium silicate-based fireproof glass.
[0061] The potassium silicate-based fireproof glass prepared in this embodiment has the following main performance characteristics as tested: visible light transmittance is 80%, haze is 3.5%, and total solar infrared thermal transmittance is 15%; fire resistance integrity is 96 min, the duration of average temperature rise on the unexposed surface ≤140℃ is 75 min, and there is no smoke release or dripping at high temperatures; after 1000 h of UV aging, the light transmittance decreases by 2.8%; after 500 h of damp heat aging, there is no delamination, no bubbling, and no ATO nanoparticle precipitation; and after 1000 cycles of -20℃ to 60℃, the near-infrared blocking rate decreases by 1.9%.
[0062] Example 3 A method for preparing potassium silicate-based fire-resistant glass includes the following steps: S1. Add tin tetrachloride and antimony acetate to ethylene glycol methyl ether, then continue to add triethanolamine and stir until completely dissolved to form a precursor mixture; wherein, the molar ratio of tin tetrachloride to antimony acetate is 10:1, the amount of tin tetrachloride added is 15% of the mass of ethylene glycol methyl ether, and the molar ratio of triethanolamine to tin tetrachloride is 0.5:1; add the hydrolysate prepared by deionized water and ethylene glycol methyl ether at a volume ratio of 1:8 dropwise to the precursor mixture at 60°C, and continue stirring for 2 hours after the addition is complete to obtain the ATO precursor solution; wherein, the molar ratio of deionized water to tin tetrachloride in the hydrolysate is 3.5:1.
[0063] S2. Mix 73wt% silica sol with 27wt% potassium hydroxide solution and stir at 40℃ for 35 min to obtain potassium silicate precursor solution.
[0064] S3. After mixing potassium silicate precursor solution, ATO precursor solution, boric acid and deionized water evenly according to the mass ratio of 1:0.1:0.04:0.35, the mixture is ultrasonically dispersed for 30 min under ultrasonic power of 200W and frequency of 25kHz. After ultrasonication, the mixture is vacuum degassed for 35 min under vacuum of -0.09MPa to obtain composite fire retardant liquid.
[0065] S4. After removing oil and impurities from the edges of the fire-facing glass layer and the unfacing glass layer, butyl rubber sealing strips are used to splice and bond the fire-facing glass layer and the unfacing glass layer to obtain a cavity with an injection port. Then, composite fireproof liquid is injected into the 5mm cavity between the two glass sheets at normal pressure. Silicone sealant is then evenly injected into the grooves formed around the fire-facing glass layer and the unfacing glass layer to seal the injection port and the grooves. After curing at 40℃ for 20 hours, potassium silicate-based fireproof glass is obtained.
[0066] The potassium silicate-based fireproof glass prepared in this embodiment has the following main performance characteristics as tested: visible light transmittance is 84%, haze is 2.5%, total solar infrared thermal transmittance is 25%; fire resistance integrity is 110 min, the duration of average temperature rise on the unexposed surface ≤140℃ is 95 min, no smoke release or dripping is generated at high temperature; after 1000 h of UV aging, the light transmittance decreases by 2%; after 500 h of damp heat aging, there is no delamination, no bubbling, and no ATO nanoparticle precipitation; after 1000 cycles of -20℃ to 60℃, the near-infrared blocking rate decreases by 1.5%.
[0067] Example 4 A method for preparing potassium silicate-based fire-resistant glass includes the following steps: S1. Stannous chloride and antimony acetate are added to anhydrous ethanol, and then acetylacetone is added and stirred until completely dissolved to form a precursor mixture. The molar ratio of stannous chloride to antimony acetate is 12:1, the amount of stannous chloride added is 18% of the mass of anhydrous ethanol, and the molar ratio of acetylacetone to stannous chloride is 2:1. A hydrolysate prepared by mixing deionized water and anhydrous ethanol at a volume ratio of 1:3 is added dropwise to the precursor mixture at 45°C. After the addition is complete, the mixture is stirred for 6 hours to obtain an ATO precursor solution. The molar ratio of deionized water to stannous chloride in the hydrolysate is 4:1.
[0068] S2. Mix 71 wt% silica sol with 29 wt% potassium hydroxide solution and stir at 45°C for 32 min to obtain potassium silicate precursor solution.
[0069] S3. After mixing potassium silicate precursor solution, ATO precursor solution, borax and deionized water evenly according to the mass ratio of 1:0.15:0.025:0.08, the mixture is ultrasonically dispersed for 50 min under ultrasonic power of 350W and frequency of 35kHz. After ultrasonication, the mixture is vacuum degassed for 40 min under vacuum of -0.1MPa to obtain composite fire retardant liquid.
[0070] S4. After removing oil and impurities from the periphery of the fire-facing glass layer and the unfacing glass layer, the fire-facing glass layer and the unfacing glass layer are spliced and bonded together using butyl rubber sealing strips to obtain a cavity containing the injection port. Subsequently, composite fireproof liquid is injected into the 5mm cavity between the two glass sheets at normal pressure. Then, silicone sealant is evenly injected into the grooves formed around the periphery of the fire-facing glass layer and the unfacing glass layer to seal the injection port and the grooves. After that, it is left to stand and cure at 55℃ for 24 hours to obtain potassium silicate-based fireproof glass.
[0071] The potassium silicate-based fireproof glass prepared in this embodiment has the following main performance characteristics as tested: visible light transmittance is 85%, haze is 2%, and total solar infrared thermal transmittance is 22%; fire resistance integrity is 100 min, the average temperature rise of the unexposed surface is ≤140℃ for 80 min, and there is no smoke release or dripping at high temperatures; after 1000 h of UV aging, the light transmittance decreases by 0.5%; after 500 h of damp heat aging, there is no delamination, no bubbling, and no ATO nanoparticle precipitation; and after 1000 cycles of -20℃ to 60℃, the near-infrared blocking rate decreases by 0.4%.
[0072] Comparative Example 1 A method for preparing potassium silicate-based fire-resistant glass includes the following steps: S1. Mix 71 wt% silica sol with 29 wt% potassium hydroxide solution and stir at 45°C for 32 min to obtain potassium silicate precursor solution.
[0073] S2. After mixing potassium silicate precursor solution, borax and deionized water evenly according to the mass ratio of 1:0.025:0.08, the mixture is ultrasonically dispersed for 50 min under ultrasonic power of 350W and frequency of 35kHz. After ultrasonication, the mixture is vacuum degassed for 40 min under vacuum of -0.1MPa to obtain composite fire retardant liquid.
[0074] S3. After removing oil and impurities from the periphery of the fire-facing glass layer and the unfacing glass layer, the fire-facing glass layer and the unfacing glass layer are spliced and bonded together using butyl rubber sealing strips to obtain a cavity containing an injection port. Subsequently, composite fireproof liquid is injected into the 5mm cavity between the two glass sheets at normal pressure. Then, silicone sealant is evenly injected into the grooves formed around the periphery of the fire-facing glass layer and the unfacing glass layer to seal the injection port and the grooves. After that, it is left to stand and cure at 55℃ for 24 hours to obtain potassium silicate-based fireproof glass.
[0075] like Figure 1 As shown, the O, Si, K, Sb and Sn elements in ATO nanoparticles are uniformly distributed in potassium silicate gel, and no obvious element enrichment or sedimentation phenomenon is observed, indicating that the three-dimensional potassium silicate network can effectively fix ATO nanoparticles and improve their dispersion stability.
[0076] Depend on Figure 2 The results showed that the ATO nanoparticles were small in size and uniformly distributed, with no obvious large particle aggregation or precipitation. This indicates that the chelation inhibitor can effectively reduce the reactivity of the metal precursor, control its hydrolysis and condensation rate, and enable the ATO nanoparticles to nucleate and grow in situ and uniformly in the system.
[0077] like Figure 3 As shown, in the cured composite fire retardant liquid, the Si-OH related absorption peak weakened, while the Si-O-Si asymmetric stretching vibration peak strengthened or shifted, indicating that the potassium silicate system underwent dehydration and condensation, forming a three-dimensional potassium silicate network. Compared with the solution without ATO precursor (Comparative Example 1), the cured composite fire retardant liquid of the potassium silicate-based fire retardant glass in Example 1 showed changes in peak intensity or position in the Si-OH and low wavenumber metal-oxygen bond related regions, indicating that the introduction of ATO nanoparticles altered the local chemical environment of the potassium silicate network, supporting interfacial interactions between the ATO nanoparticles and the three-dimensional potassium silicate gel network.
[0078] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range, as well as any value between the two endpoints, can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.
Claims
1. A method for preparing potassium silicate-based fire-resistant glass, characterized in that, Includes the following steps: In a liquid environment, tin-containing precursors, antimony-containing precursors, and chelation inhibitors are mixed and subjected to coordination reactions to form metal complexes with organic groups coated on the surface, thus obtaining a precursor mixture; the molar ratio of tin-containing precursors to antimony-containing precursors is 8~12:1, and the molar ratio of chelation inhibitors to tin-containing precursors is 0.5~2:
1. A hydrolysate, consisting of a mixture of water and an organic solvent, is added dropwise to a precursor mixture to induce a hydrolysis-condensation reaction, generating an intermediate containing metal-hydroxyl groups. This intermediate then undergoes intermolecular dehydration or deacidification condensation reactions to generate antimony-doped tin dioxide nanoparticles containing metal-hydroxyl groups, yielding an ATO precursor solution. In the hydrolysate, the volume ratio of water to organic solvent is 1:3~8, and the molar ratio of water to tin-containing precursor is 2~4:
1. A composite fire retardant liquid is obtained by mixing potassium silicate precursor solution, ATO precursor solution, crosslinking agent and water. The composite fire retardant liquid is then filled into the cavity formed by bonding two layers of glass sheets, sealed and allowed to solidify. During the solidification process, the composite fire retardant liquid transforms from a liquid sol to a solid gel. Potassium silicate undergoes condensation to form a three-dimensional potassium silicate network. Simultaneously, the metal-hydroxyl groups on the surface of antimony-doped tin dioxide nanoparticles undergo dehydration condensation with the Si-OH groups on the three-dimensional potassium silicate network to form a gel containing Si-O-Sn bonds, Si-O-Sb bonds and Sb-O-Sb bonds, thus obtaining potassium silicate-based fire retardant glass.
2. The preparation method according to claim 1, characterized in that, The mass ratio of potassium silicate precursor solution, ATO precursor solution, crosslinking agent and water is 1:0.02~0.25:0.005~0.04:0.08~0.
35.
3. The preparation method according to claim 1, characterized in that, The conditions for the coordination reaction are: stirring at room temperature for 3 to 5 hours.
4. The preparation method according to claim 1, characterized in that, The conditions for the hydrolysis-condensation reaction are: stirring at 30℃~60℃ for 2h~6h.
5. The preparation method according to claim 1, characterized in that, The curing conditions are: static curing at 40℃~60℃ for 12h~24h.
6. The preparation method according to claim 1, characterized in that, The potassium silicate precursor solution is prepared by mixing silica sol and potassium hydroxide solution; and in the potassium silicate precursor solution, the mass fraction of silica sol is 68wt%~73wt%, and the mass fraction of potassium hydroxide solution is 27wt%~32wt%.
7. The preparation method according to claim 1, characterized in that, The chelation inhibitor is selected from acetylacetone, diethanolamine, or triethanolamine.
8. The preparation method according to claim 1, characterized in that, The crosslinking agent is selected from one or two of borax and boric acid, and its average particle size is 20μm~75μm.
9. The preparation method according to claim 1, characterized in that, The glass substrate comprises: SiO2 70wt%~75wt%, Na2O 12wt%~15wt%, CaO 7wt%~10wt%, MgO 2wt%~5wt%, and Al2O3 0.5wt%~2.5wt%.
10. A potassium silicate-based fireproof glass prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Heat insulation type fireproof glass and manufacturing method thereof
CN119463754A
Anti-reflection heat-insulation fireproof glass and preparation method thereof
CN120902364A
Energy-saving nanometer fireproof heat-insulating glass
CN218535900U
Temperature-dependent fireproof ceiling glass
CN221497313U